Responding to terrorism in South Asia - Muni, S. D. (ed.) (New Delhi, 2006)
Published in association with Regional Centre for StrategicStudies, Colombo Even though South Asia had a long and diverseexperience of dealing with terrorism, post 9/11 a sense of urgencyand seriousness has been reinforced with regard to it at the globallevel. The focus in this timely volume is on the strategic evolvedby the South Asian states in responding to the challenge ofterrorism. It is inevitable, however, that while looking at thestrategies, essential characteristics of terrorism are alsounderstood and explained as the nature of terrorism faced in eachof the South Asian countries has its own specific aspects. Thestudy is divided into two sections. In the first section, the wayin which each of the South Asian states have responded toterrorism. Has been studied carefully. In the second section, someof the comparative aspects of the region perspective, such as therole of civil societies, consequences of strategies pursued, roleof the third parties, and political economy of terrorism andresponding strategies have been taken up for discussion andanalysis. There is also a data paper on South Asian terrorismincluded at the end. Contributors include Ajay Sahni, Samina Ahmed,Abul Kalam, Ayesha Siddiqa, Deepak Thapa among many others.
Keywords: Terrorism-India